Direct Observation and Analysis of Bacterial Growth on an Antimicrobial Surface - Yamada, Hiroyuki (American Society for Microbiology (ASM), 2010)
Cells of Escherichia coli NBRC 3972 and Staphylococcus aureus NBRC 12732 were inoculated onto an agar (1.5%) medium varying in nutrient concentration from full strength of the nutrient broth (NB) to 1/10 NB. Immediately thereafter, the inoculated agar was placed on antimicrobial and nonantimicrobial surfaces in such a way that the microbial cells came into contact with these surfaces. Cell growth was directly observed under a microscope, and the growth rate constant of the cells was measured based on the increase in the area of the colonies formed by the growing cells. On the antimicrobial surface, the growth rate constant decreased at lower nutrient concentrations for both E. coli and S. aureus cells, whereas it showed little change on the nonantimicrobial surface. It was supposed that either the nutrient uptake or the nutrient utilization efficiency was retarded by the antimicrobial surface. At the lowest nutrient concentration examined in the present study, 1/10 NB, the cells could hardly grow on the antimicrobial surface, indicating that the surface would be sufficiently active in preventing bacterial growth under normal usage conditions, such as the wet areas of a kitchen. It was also revealed that the antimicrobial surface could prevent the division of cells either during the growth stage or before the onset of growth.